Pengaruh Pursed Lips Breathing (PLB) Terhadap Nilai Forced Expiratory Volume In One Second (FEV1) Pada Penderita Penyakit Paru Obstruksi Kronis Di Rs Paru Dr Ario Wirawan Salatiga - DEWI, Stefanie Kusuma; , Agus Widodo, S.Fis, M.Kes; , Isnaini Herawati, SSt. FT, M. Sc (2015)
Introduction: Chronic Pulmonary Obstruction is kinds of chronic pulmonary disorder which commonly appear from the limit of oxygen flow to the lungs and not completely reversible, it is progresif, and usually happened from pulmonary inflamation processes caused by dangerous gas which give systemic disorder. This disorder can be prevented and cured. The main causes of this disease are smoking, smoke, pollution of fire, and dangerous gas element. Objective: This research is done to find out the relationship of Pursed lips breathing Toward Forced Expiratory Volume of One Second (FEV1) Score for Chronic Pulmonary Obstruction At Pulmonary Hospital Dr Ario Wirawan Salatiga. Method: This research was done by using Quasi Experimental Design with pre test and post test design. The research population of this research was 10 people with 10 people as the sample taken according to inclusion and exclusion. The data taken were not normally distributed, statistical test done by non parametric test. Result: Based on the analysis done by using Wilcoxon Test showed that the value of p ≤ 0, 05 so that Ho is denied dan Ha is accepted. It means that there is a relationship of Pursed Lips Breathing (PLB) Toward Forced Expiratory Volume of One Second (FEV1) Score for Chronic Pulmonary Obstruction at Pulmonary Hospital DR Ario Wirawan Salatiga. It is expected that this research can give additional information to the readers or other researcher, especially Chronic Pulmonary Obstruction Patient.